Bioethics Without Theory? - Holm, Søren (Cambridge quarterly of healthcare ethics, 2024)
The question that this paper tries to answer is Q: "Can good academic bioethics be done without commitment to moral theory?" It is argued that the answer to Q is an unequivocal "Yes" for most of what we could call "critical bioethics," that is, the kind of bioethics work that primarily criticizes positions or arguments already in the literature or put forward by policymakers. The answer is also "Yes" for much of empirical bioethics. The second part of the paper then provides an analysis of Q in relation to "constructive bioethics," that is, bioethics work aimed at providing an argument for a particular position. In this part, it is argued that a number of the approaches or methods used that initially look like they involve no commitment to moral theory, nevertheless, involve such a commitment. This is shown to be the case for reflective equilibrium, mid-level theory, the use of theory fragments, and argument by analogy.